Effect Of Hormone Therapy On Fertility And Plasma Minerals Profile In Repeat Breeding Gir Cows - Parmar, Sachin V.; Patel, J.A.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
This study was carried out on 24 repeat breeding cows of Gir breed divided at random in to four groups, 6 animals in each. Animals of Group I were treated with single i/m injection of 0.02 mg buserelin acetate and Group II with single i/m injection of 1500 IU hCG immediately after natural breeding, while animals of Group III were administered with 500 mg of hydroxy-progesterone caproate on day 6 of natural breeding and those of Group IV bred without any treatment served as control. Blood plasma samples were collected on day 0 (oestrus) and then at weekly interval up to 6 weeks post-breeding/ treatment and were stored at -20°C. The first service conception rates obtained following 3 treatments were 50.00, 83.33 and 50.00 %, respectively, with an overall mean of 61.11 %. These were significantly higher (P
Keywords: Gir cows; repeat breeding; hormone therapy; plasma mineral profile